Διερεύνηση των ψυχομετρικών ιδιοτήτων της κλίμακας επιθανάτιας εμπειρύας (NDES) - Κυριάκου, Κυριάκος (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The improvement in survival after cardiac arrest, because of the modern resuscitation techniques, increase the frequency of the phenomenon of near death experience in patients with cardiac arrest. This phenomenon seem to affect these patients and the detection of them will contribute to a better nursing care through a holistic approach. This study explores the psychometric properties of a measuring tool for this particular phenomenon with the view to create a background for further investigation in Cyprus. Aim: The purpose of this study is to investigate the psychometric properties of near death experience scale in Greek. Method: After retaining the authorization by the manufacturer, the questioner translated into Greek language through double reverse translation. For completing the questioner we used a sample of consecutive patient who were resuscitated from cardiac arrest. The approach of these patients was done via personal communication with the researcher for information and consent. Test retest reliability , Cronbach’s alpha for internal consistency and exploratory factor analysis was performed. Furthermore we examined the association between demographic characteristics and the probability of near death experience with a logistic regression model. Results: The near death experience scale has high internal consistency both as a whole (Cronbach’s a= 0,91) and in the four subscales(cognitive-0,82 , affective-0,90, paranormal-0,74 and transedental-0,92) . In addition to this, scale has also high test retest reliability( r = 0,91 p< 0.0001). Factor analysis reproduced exactly the same four subgroups of the original scale version. The communality explained amounts 44,10%, 12,50%, 9,50 and 8,70% for the transcendental ,paranormal, affective and cognitive subgroup respectively . The question loadings on four factors ranged from 0,76-0,92. From the total of 64 individuals 14(21,9%) had near death experience: 5(7,8%) had cognitive near death experience, 7(10,9%) had transcendental , 1(1,6%) had affective and 1(1,6%) had paranormal. Finaly association between near death experience with the level of training (OR= 0,027) and the duration of hospital treatment(OR=1,051) was detected. Conclusion: The Greek issue of near death experience scale has good psychometric properties and can be used in detecting people who experienced the specific phenomenon with the view to achieve a holistic approach for nursing patients with near death experiences.
Keywords: Psychometric Properties; Scale NDE; Ψυχομετρικές Ιδιοτήτες; Κλίμακας Επιθανάτιας Εμπειρίας